Damage to flat-based wine storage tanks in the 2013 and 2016 New Zealand earthquakes. (May 2020) - Yazdanian, Mohsen; Ingham, Jason M.; Kahanek, Christopher; Dizhur, Dmytro
Abstract: In-field post-earthquake damage assessment of wineries was conducted following the 2013 Seddon earthquake (Mw 6.5), the 2013 Lake Grassmere earthquake (Mw 6.6), and the 2016 Kaikōura earthquake (Mw 7.8) in New Zealand. These assessments provided an opportunity to assemble the largest database ever collected on the earthquake performance of wine storage tanks. Observations documented and discussed herein highlight detailed statistics regarding the earthquake performance of 546 flat-based wine storage tanks from the 2013 earthquakes and of 802 flat-based wine storage tanks from the 2016 earthquake. Damage data revealed that of the 546 inspected wine storage tanks following the 2013 earthquakes, 69% sustained damage, and that of the 802 inspected wine storage tanks following the 2016 earthquake, 73% sustained damage. In the 2013 earthquakes the tank base shell (39%) and anchor (47%) parts of the flat-based wine tanks sustained the largest proportion of damage, while due to resilience measures implemented following the 2013 earthquakes, damage to tank base shells and to tank anchors in the 2016 earthquakes reduced to 32% and 23% respectively, and instead damage to the barrel (54%) and cone (43%) parts of flat-based wine tanks was identified as being most significant. Indenting of the tank barrel due to impact from a catwalk during the 2013 (10%) and 2016 (24%) earthquake events was identified as the most crucial failure type that caused damage to tank barrels. Highlights: The largest earthquake damage database to the flat-based wine storage tanks is presented herein. The study details damage to different tank parts for a total of 1348 flat-based wine tanks. The available information allowed for extensive parametric comparison of the seismic performance of wine tanks. Seismic performance of wine tanks was compared following the 2013 earthquakes and the 2016 earthquake.